Biomimetic Redox-Responsive Mesoporous Organosilica Nanoparticles Enhance Cisplatin-Based Chemotherapy - Chen, Fangman; Zhang, Fan; Wang, Yanbin; Peng, Jiahui; Cao, Lei; Mei, Qian; Ge, Mingfeng; Li, Li; Chen, Meiwan; Dong, Wen-fei; Chang, Zhimin (Frontiers in Bioengineering and Biotechnology, 2022)
Cisplatin-based chemotherapy is dominated in several cancers, however, insufficient therapeutic outcomes and systemic toxicity hamper their clinical applications. Control release of cisplatin and reducing the inactivation remains an urgent challenge to overcome. Herein, diselenide-bridged mesoporous organosilica nanoparticles (MON) coated with biomimetic cancer-cell-membrane were tailored for coordination-responsive controlled cisplatin delivery and GSH depletion to strengthen Pt-based chemotherapy. Cisplatin-loaded MON (MON-Pt) showed high loading capacity due to robust coordination between selenium and platinum atom and preventing premature leakage in normal tissue. MON-Pt exhibited a controlled release of activated cisplatin in response to the redox tumor microenvironment. Meanwhile, MON-Pt containing redox-responsive diselenide bonds could efficiently scavenge intracellular inactivation agents such as GSH to enhance Pt-based chemotherapy. 4T1 breast cancer cell membranes cloaked MON-Pt (MON-Pt@CM) performed efficient anti-cancer performance and low in vivo system toxicity due to long blood circulation time and high tumor accumulation benefiting from the tumor targeting and immune-invasion properties of the homologic cancer cell membrane. These results suggest a biomimetic nanocarrier to control release and reduce the inactivation of cisplatin for efficient and safe Pt-based chemotherapy by responding and regulating the tumor microenvironment.